Provocauteurs and Provocations : Screening Sex in 21st Century Media - San Filippo, Maria (Book collections on Project MUSE., 2021)
Throughout this edgy volume, San Filippo examines a myriad of controversial strategies--including ""real sexscenes, scandalous marketing campaigns, full-frontal nudity, troubling texts, and divisive figures--to reveal the critical role that sexual provocation plays as a promotional strategy and authorial signature within the contemporary media landscape.